Membangun Sistem Informasi Manajemen pada PT. Bunga Mekar Industri - Farhan, Ali (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
This study based on action research aims to formulate an effective work policy for PT Bunga Mekar Industri. Action research is an attempt to determine the performance of a process to be more effective (Farhan, 2017). PT Bunga Mekar Industri as a national pellet company in Jember found that the company did not have sufficient information for analysis, the results of this study were; 1) Making document of goods receipt, cash in, goods out, cash out; 2) make procedures for all Company activities, including finance, inventory, procurement, and production; 3) making production policies and calculating production costs to be able to present productivity reports to management.